2009
DOI: 10.1002/cphc.200900091
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Elongated Magnetic Particles: Magnetization and Friction Coefficient Anisotropies

Abstract: β‐turns belong to the most important secondary structure elements in proteins. On the basis of density functional calculations, vibrational Raman optical activity signatures of different types of β‐turns are established and compared as well as related to other signatures proposed in the literature earlier. Our findings indicate that there are much more characteristic ROA signals of β‐turns than have been hitherto suggested. These suggested signatures are, however, found to be valid for the most important type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 126 publications
2
46
0
Order By: Relevance
“…In recent years several studies were performed on magnetic nano-particles and colloids that deviate from the usual model of a dipole placed in the center of a spherical particle. Some examples, in particular, are dumbbells [2], magnetic core-shell particles, [3], elongated ferro-particles [4], and colloidal particles with a magnetic cap [5]. These models allow to fine-tune various aspects of interactions in the system.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years several studies were performed on magnetic nano-particles and colloids that deviate from the usual model of a dipole placed in the center of a spherical particle. Some examples, in particular, are dumbbells [2], magnetic core-shell particles, [3], elongated ferro-particles [4], and colloidal particles with a magnetic cap [5]. These models allow to fine-tune various aspects of interactions in the system.…”
Section: Introductionmentioning
confidence: 98%
“…Development of such structures is resulting in the increase of the suspension viscosity and transition from Newtonian to pseudoplastic behaviour appears with certain level of the yield stress [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Goldhawk et al (2012) reviewed the magnetosomes as a reporter of gene expression in MRI and found that their suitability and superiority for development of reporter gene expression for MRI. Vereda et al (2009) also reported the use of magnetosomes as contrast agents for MRI. In their patent claim, Gambhir et al (2010) disclosed the use of M. magneticum AMB-1 as the MRI contrast agent and a method of detecting tumors in a subject by MTB enhancement of the positive contrast of MRI.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 96%